기록관리기관은 문화유산기관인가? 저작권법의 고아저작물 예외규정에서 기록관리기관 배제 문제 고찰 - 이호신(Hosin Lee); 정경희(Kyoung Hee Joung) (Journal of Records Management & Archives Society of Korea, 2020)
This study analyzed the issues on Article 35-4 of the Copyright Act of Korea, a new provision on the use of orphan works. The new provision was compared to other related provisions, and considerations were suggested for their improvement. The main results are summarized as follows: (1) Article 35-4 is contradictory to other provisions and needs further revisions as it limits the subject of application to the main body of operation and applies only to some libraries, museums, and galleries through its ordinances; (2) a new provision on the use of orphan works must be applied to archives to harmonize with Article 31 and use the interconnection between cultural heritage institutions more beneficially; and (3) considering that there are many unpublished works in the archives, Article 35-4 should be revised to also be applicable to those works. 본 연구는 저작권법 제35조의 4에 신설된 고아저작물 이용에 대한 예외규정의 문제점을 분석하고 그 개선을 위한 고려사항을 제안하기 위하여 기존 관련규정과 비교하여 분석하였다. 본 연구의 분석결과와 제안은 다음과 같다. (1) 본 예외규정이 운영 주체라는 요건으로만 적용대상 기관을 제한하고 하위법을 통하여 도서관, 박물관, 미술관에만 적용하는 것은 이 규정의 도입취지에 부합하지 않으므로 기록관리기관이 포함될 수 있도록 개정이 필요하다. (2) 저작권법 제31조 등과의 조화나 문화유산기관 소장자료가 상호 연계되어 가치있게 이용될 수 있도록 법 개정이 이루어져야 한다. (3) 기록관리기관에는 무수히 많은 미공표저작물이 보관되어 있음을 고려하여 고아저작물 예외규정이 미공표저작물에도 적용되도록 개정될 필요가 있다.